Adult health outcomes in South Africa: a longitudinal analysis of the causes of disease among rural-rural migrants. - Thokwane, Lebohang Zinhle (My University, 2022)
Background: Rural-rural migration refers to the process whereby people move from one rural area within a national boundary to another. This is often for the; family, retirement or economic reasons. The health and well-being of adults who participate in rural-rural migration in South Africa has become a crucial issue. It may also have an impact on the well-being of the entire population. Rural migration – migration to, from and between rural areas is a large component of both internal and international migration flows. Some 250 million people have migrated internationally during their lifetime, many originating from rural areas. Even more people have migrated internally, with more than 1 billion in developing countries alone. Moreover, in a sample of 31 developing countries, more than half of the people living in rural areas during their childhood migrated internally. 80% of internal moves involve rural areas, but less than 30% constitute rural–urban migration, while the rest are rural–rural or urban–rural movements. Many refugees and internally displaced people come from rural areas, and many are hosted in rural areas as well. For example, more than 80% of refugees in sub-Saharan Africa are found in rural areas. Not all migration is permanent or longterm. However, little is known about the causes of diseases among older people who are mobile. Therefore, this study aimed at filling the gap on causes of diseases (diabetes, hypertension, tuberculosis) among adults who move from one rural to another in South Africa. Objectives: To identify the levels and socio-economic determinants of disease outcome among rural-rural migrants aged 24-80 years. The study population was made of adults who were mobile. Methodology: This longitudinal study used wave 1 (2008) and wave 5 (2017) of the South African National Income Dynamics Study (SA NIDS). Cross tabulations, regression models were used and in wave 1 adults who did not have a disease were identified and followed through to wave 5 if they have moved to another rural area and measured their diseases status. Chi-square tests were used to detect significant level in disease outcome. Results were presented with confidence intervals of 95% probability. Binary logistic regression model was used while controlling for several covariates. The choice of using the regression model was informed by that, the outcome variable was dichotomous. Four different models with different disease outcome were used. Results: This study’s findings showed that hypertension was higher among the females than males. One of the reasons for this could be behavioural risk factors such as physical inactivity. The current study indicated a high prevalence rate of diabetes among adults and those in the older age cohort. Older adults are more likely to have a diabetic, tuberculosis or hypertensive disease. This may be because older adults tend to be less attentive to their health as they grow older. Conclusion: South Africa is confronted with several major health challenges simultaneously, including a high burden of infectious diseases and non-communicable diseases. The results show that there are differences in the causes of diseases in the study area between the rural-rural migrants. Aside from family size of migrants and smoking, the prevalence of diseases showed significant differences of in, behavioural, and personal variables. Changes in lifestyle and diet in the context of globalization have contributed to a shift in health patterns. A rigorous effort is required to change the course of the rising disease outcome burden in the country; the price of delay will otherwise be devastating.
A research project submitted to the Faculty of Humanities, School of Social Sciences, University of Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Arts in Demography and Population Studies, 2021